2013
DOI: 10.1088/0067-0049/206/2/14
|View full text |Cite
|
Sign up to set email alerts
|

Optical Counterparts of the Nearest Ultraluminous X-Ray Sources

Abstract: We present a photometric survey of the optical counterparts of ultraluminous X-ray sources (ULXs) observed with the Hubble Space Telescope in nearby ( 5 Mpc) galaxies. Of the 33 ULXs with Hubble & Chandra data, 9 have no visible counterpart, placing limits on their M V of ∼ -4 to -9, enabling us to rule out O-type companions in 4 cases. The refined positions of two ULXs place them in the nucleus of their host galaxy. They are removed from our sample. Of the 22 remaining ULXs, 13 have one possible optical count… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
104
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 125 publications
(280 reference statements)
12
104
1
Order By: Relevance
“…This resulted in a sample of five ULXs, details of which are shown in Table 1. For four of the five sources in the sample, Gladstone et al (2013) identified only a single potential optical counterpart in the HLA images; the exception to this was NGC 1313 X-2, which had two potential counterparts. Here, we use only the counterpart to NGC 1313 X-2 previously identified by Liu et al (2007) and confirmed by Grisé et al (2008).…”
Section: Sample Selectionmentioning
confidence: 97%
See 4 more Smart Citations
“…This resulted in a sample of five ULXs, details of which are shown in Table 1. For four of the five sources in the sample, Gladstone et al (2013) identified only a single potential optical counterpart in the HLA images; the exception to this was NGC 1313 X-2, which had two potential counterparts. Here, we use only the counterpart to NGC 1313 X-2 previously identified by Liu et al (2007) and confirmed by Grisé et al (2008).…”
Section: Sample Selectionmentioning
confidence: 97%
“…To carry out broad-band spectral modelling, we require both X-ray and optical data. Thus, we selected all of the ULXs with broadened disc spectra in Sutton et al (2013), which also had optical counterparts identified by Gladstone et al (2013) in Hubble Space Telescope (HST) Hubble Legacy Archive (HLA 4 ) data. This resulted in a sample of five ULXs, details of which are shown in Table 1.…”
Section: Sample Selectionmentioning
confidence: 99%
See 3 more Smart Citations